Clinical Consequences of Misinterpretations of Neuroradiologic CT Scans by On-CallRadiology Residents - Lal, Nirish R.; Murray, Uwada M.; Eldevik, O. Petter; Desmond, Jeffrey S. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Studies have looked at the accuracy of radiologic interpretations by radiology residents as compared with staff radiologists with regard to emergency room plain films, emergency room body CT scans, and trauma head CT scans; however, to our knowledge, no study has evaluated on-call resident interpretations of all types of neuroradiologic CT scans. Both as a part of our departmental quality control program and to address concerns of clinical services about misinterpretation of neuroradiologic CT scans by on-call radiology residents, we evaluated the frequency of incorrect preliminary interpretations of neuroradiologic CT scans by on-call radiology residents and the effect of such misinterpretations on clinical management and patient outcome.METHODS: As determined by the staff neuroradiologist the next day, all potentially clinically significant changes to preliminary reports of emergency neuroradiologic CT scans rendered by on-call radiology residents were recorded over a 9-month period. A panel of neuroradiologists reviewed and graded all the changed cases by consensus. An emergency department staff physician reviewed medical records of all submitted cases to determine clinical consequences of the misinterpretations.RESULTS: Significant misinterpretations were made in 21 (0.9%) of 2388 cases during the study period. There was a significant change in patient management in 12 of the cases, with a potentially serious change in patient outcome in two cases (0.08%).CONCLUSION: On-call radiology residents have a low rate of significant misinterpretations of neuroradiologic CT scans, and the potential to affect patient outcome is rare.